Criticisms on Amnesty for People with Mental Disabilities in Indonesia: Transformative Effort from Substitutive to Supportive Decision Making - Syafi'ie, M. (KnE Social Sciences, 2023)
The community of persons with disabilities currently disputes the regulation on amnesty. Amnesty is considered discriminatory and violates the rights of persons with disabilities, especially those with mental disabilities. The amplification rule, which means that persons with disabilities do not have legal capacity, is considered inconsistent with the Convention on the Rights of Persons With Disabilities (CRPD), which substantively stipulates that persons with disabilities do have the legal capacity and that the government is obliged to take measures to provide access to the necessary support that is needed, known as the supportive decision-making system. Keywords: Persons with Disabilities, Amnesty, Supportive Decision Making